The gendered impacts of income fluctuations on household departure, labor supply, and human capital decisions: Evidence from Kyrgyzstan - Kosec, Katrina; Song, Jie; Zhao, Hongdi; Holtemeyer, Brian (International Food Policy Research Institute, 2021)
How do fluctuations in income affect labor supply decisions, and how do their effects differ by gender? We analyze data from a 13-year rolling panel in Kyrgyzstan spanning 2004—2016. We address the endogeneity of fluctuations in income to labor supply decisions using a household fixed effects model and exploiting region-level changes over time in growth rates of different sources of revenue and production costs to which households have varying levels of baseline exposure. We find that reductions in income relative to the median spur departure from the household (e.g., due to migration or new household formation), with smaller impacts on women than men. However, women’s labor supply at the origin is affected significantly more than that of men, with short-term increases in hours of employment and declines in home production and other activities. Reductions in income also fuel temporary migration for both genders, with larger effects for men, and widen the gender gap in pursuit of non-compulsory education.